It had to be you [compact disc, unabridged] - Clark, Mary Higgins; Burke, Alafair (Clark, Mary Higgins. Under suspicion novel., 2024)
The two identical brothers seemed perfect in every way, handsome, intelligent, popular, until a shocking summer night when one brother killed his parents in cold blood while the other brother had an iron-clad alibi. But which twin was where during the murders? And is it possible the two of them planned the perfect crime together? Years later, the twins are long estranged, each of them claiming to be convinced that the other is responsible for the death of their parents. Married now with children of their own, they may finally be ready to clear one name at the expense of the other and turn to Laurie Moran and her team to reinvestigate their parents' murder. But as the Under Suspicion crew gets closer to the truth, the danger that was assumed to be left in the past finds its way into the present.